Interferon-α suppresses invasion and enhances cisplatin-mediated apoptosis and autophagy in human osteosarcoma cells - ZHAO, JUN (D.A. Spandidos, 2014)
Interferon (IFN)-α is generated in response to viral infections and is used clinically in the therapy of a variety of viral infections and cancers. The present study investigated whether IFN-α could inhibit the invasive ability of osteosarcoma cells using a Matrigel invasion assay. In addition, the osteosarcoma cells were treated with cisplatin and/or IFN-α. Apoptosis and autophagy were assessed using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, Hoechst 33258 staining, flow cytometry assay, acridine orange staining, green fluorescent protein-LC3 dot assay and transmission electron microscopy. Further analysis revealed that the efficacy of cisplatin was enhanced by the addition of the cytokine, IFN-α. These results indicate that the combination therapy of chemotherapeutics and IFN-α is a new approach for osteosarcoma, which requires validation by experiments in vivo.